1,4-Butanediol intoxication: a case report - Castro, André Lobo (2018)
Gamma-hidroxibutyric acid (GHB) is an endogenous compound with known action at the neural level. Its psychoactive effects led to an illicit use context including recreational purposes, muscle building effects in bodybuilders and drugs-facilitated crimes, specifically, in sexual assaults. Besides the use of the main compound, there are precursors, like Gammabutyrolactone (GBL) and 1,4-butanediol (1,4-BD), usually non controlled substances, allowing a much easier way to obtain the target-compound. The authors present the first reported intoxication case in Portugal with 1,4-Butanediol, including the quantification of GHB and GHB-GLUC in serum, by GC-MS/MS TQD. A male, 25 years old, entered in coma at the hospital emergency room, with the suspicion of an intoxication due to an unknown liquid ingestion. The forensic toxicology lab was asked to collaborate in order to identify the possible substance(s) involved and provide adequate treatment to the patient. The suspicious liquid and a serum sample were sent by the hospital and analysed by GC-MS-single quadrupole and GC-MS/MS TQD, respectively. A methodology including protein precipitation and GC-MS/MS TQD analysis was used to detect and quantify GHB and GHB-GLUC in serum. Toxicological analysis revealed the presence of 1,4-Butanediol in the liquid and GHB [171 mg/L] and GHB-GLUC [13,7 mg/L] in serum.The victim reverted the coma state with no neurological sequelae. This was the first detected case in Portugal with 1,4-Butanediol, suggesting that it is important to be aware that consumers have different options to acess illicit compounds, such as GHB. On the other hand, GHB-GLUC was identified and quantified for the first time in a real case sample, due to intoxication. This case highlights the importance of analyzing all samples for active compounds, percursors and metabolites that can lead to the main intoxication origin.